Evidence for the occurrence of gingival recession and non‐carious cervical lesions as a consequence of traumatic toothbrushing. (April 2015) - Heasman, Peter A.; Holliday, Richard; Bryant, Andrew; Preshaw, Philip M.
Abstract: Aim: To identify the best available evidence for the effect of toothbrushing on the initiation and progression of gingival recession and non‐carious cervical lesions (NCCLs). Methods: A protocol was developed for the questions: Does traumatic toothbrushing, compared to normal toothbrushing, lead to an increased prevalence of non‐inflammatory gingival recession? [FQ1] and NCCLs? [FQ2]. The search covered four electronic databases. Bibliographies of review articles, relevant texts, World and European Workshops were screened. Hand searches were performed of the Journals of Clinical Periodontology, Periodontology, Periodontal Research and IADR abstracts. Results: A meta‐analysis included 159 subjects and showed that subjects who used MTBs (manual toothbrush) had greater gingival recession after 12 months when compared with those using PTBs (powered toothbrush). Thirteen cross‐sectional studies identified the most frequent toothbrushing factors associated with gingival recession as being toothbrushing frequency, a horizontal or scrub toothbrushing method, bristle hardness, toothbrushing duration and the frequency of changing a toothbrush. The principal toothbrushing factors associated with NCCLs were toothbrushing method and frequency. Conclusion: The data to support or refute the association between toothbrushing and gingival recession and NCCLs remain largely inconclusive.